Surgical Site Infections after Elective Surgery in Pakistan: SURGIPAK Study - Asif Zafar Malik (Journal of Rawalpindi Medical College, 2015)
Background: To determine the incidence of surgical site infections(SSIs), and to document the causative organisms, duration of hospital stay, and therapeutic class of antibiotics administered in surgical prophylaxis in patients undergoing elective surgeries in Pakistan. Methods: In this multicenter observational study surgeons were randomly selected. Surgical data from each investigator was collected from surgeries performed within a period of three months prior to the last month preceding the site initiation date. Patients 18 years of age or above, who had undergone elective surgeries that included gastrointestinal, biliary, pancreatic, urogenital, abdominal hernia, gynecologic procedures including caesarean section, were selected. The investigator collected data on last 10 consecutive patients preferably in the month between -2 and -1.Recruitment list of 10% investigators was validated against the Operation theatre (OT) list. For each patient, data on demography, surgical information, antibiotic usage, SSI information and laboratory analysis was captured.The data was collected on a standardized case report form (CRF). The CRF was completed by the investigator/study coordinator. Results: Out of 858 patients, 71% were females. The mean age was 38.8±13.1 years. Three most common surgeries were gynecological including caesarean section (42.4%, 364/858), biliary (19.8%, 170/858) and abdominal hernia (18.4%, 158/858). In most cases (54.5%, 468/858), the duration of surgery was between 1–4 hours, and a majority (67.7%, 581/858) were classified as clean surgeries. In total, 6.5% patients (56/858) developed SSIs (95% confidence interval 5.1%-8.4%). All patients undergoing pancreatic surgery (n=3) developed SSI. Of the patients who developed SSIs 50% (28/56) developed it in post operative hospitalization period. The most common organisms isolated were Staphylococcus aureus (37.5%, 21/56), Escherichia coli (30.4%, 17/56) and Enterobacter (5.4%, 3/56). Significant mean difference (8.3±10.3 vs 3.3±2.9 days, p <0.001) in duration of hospital stay was observed in patients who developed SSI in comparison to those who did not. Cephalosporin (73.2%) was the most common therapeutic class used for prophylaxis, with third generation cephalosporin used in 60.7%. Conclusions: Periodic reporting of SSI rates is essential for international benchmarking and for strategizing efforts in reducing the associated healthcare burden in developing nations.